2020
DOI: 10.3390/ijms21207679
|View full text |Cite
|
Sign up to set email alerts
|

Y-27632 Induces Neurite Outgrowth by Activating the NOX1-Mediated AKT and PAK1 Phosphorylation Cascades in PC12 Cells

Abstract: Y-27632 is known as a selective Rho-associated coiled coil-forming kinase (ROCK) inhibitor. Y-27632 has been shown to induce neurite outgrowth in several neuronal cells. However, the precise molecular mechanisms linking neurite outgrowth to Y-27632 are not completely understood. In this study, we examined the ability of Y-27632 to induce neurite outgrowth in PC12 cells and evaluated the signaling cascade. The effect of Y-27632 on the neurite outgrowth was inhibited by reactive oxygen species (ROS) scavengers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
1
3
1
Order By: Relevance
“…To evaluate the role of Akt in neurite growth modulated by ROS, we inhibited the Akt activity with LY294002, a PI3K inhibitor (Vlahos et al., 1994) at 1 or 2 DIV and we measured the neurite outgrowth after 24 h. As mentioned previously, the antioxidant treatments increased the p‐Akt and decreased the neurite growth, suggesting a negative effect of Akt in neurite growth as reported as reported in other models (Bang et al., 2001; Miyamoto et al., 2013). On the other hand, contrary to what was found in DGR neurons (Hervera et al., 2018) and PC12 cells (Park et al., 2020), in the present study the inhibition of Akt activity did not alter the inhibitory effect of antioxidants on the neurite growth in cells treated at 1 or 2 DIV and enhanced the effect of antioxidants at 1 DIV on the number of branches per cell. We therefore found opposite results between the effect of antioxidants on Akt activation (measured by an increase in p‐Akt) and the effect of Akt activation on neurite growth.…”
Section: Discussioncontrasting
confidence: 99%
“…To evaluate the role of Akt in neurite growth modulated by ROS, we inhibited the Akt activity with LY294002, a PI3K inhibitor (Vlahos et al., 1994) at 1 or 2 DIV and we measured the neurite outgrowth after 24 h. As mentioned previously, the antioxidant treatments increased the p‐Akt and decreased the neurite growth, suggesting a negative effect of Akt in neurite growth as reported as reported in other models (Bang et al., 2001; Miyamoto et al., 2013). On the other hand, contrary to what was found in DGR neurons (Hervera et al., 2018) and PC12 cells (Park et al., 2020), in the present study the inhibition of Akt activity did not alter the inhibitory effect of antioxidants on the neurite growth in cells treated at 1 or 2 DIV and enhanced the effect of antioxidants at 1 DIV on the number of branches per cell. We therefore found opposite results between the effect of antioxidants on Akt activation (measured by an increase in p‐Akt) and the effect of Akt activation on neurite growth.…”
Section: Discussioncontrasting
confidence: 99%
“…In studies with Fasudil, a ROCK inhibitor, the authors observed an in vitro induction of neurogenesis in mouse neural stem cells [ 61 ], and also protection against oxygen–glucose deprivation in primary neurons of the hippocampus of mouse embryos [ 62 ]. Similar results were also observed for another ROCK inhibitor, Y-27632, which induced neurite outgrowth in PC12 cells by activating AKT phosphorylation cascades [ 63 ]. In another study, a benzofuran derivative (MBPTA), a ROCK inhibitor, protected SH-SY5Y cells against induced-oxidative stress, possibly through PI3K/Akt activation [ 64 ].…”
Section: Discussionsupporting
confidence: 82%
“… 49 Similarly, in PC12 cells, neurite outgrowth increased after 2 or 3 h of treatment with Y-27632. 50 In the peripheral nervous system, activation of ROCK results in contractility and growth cone retraction. 51 Although tension has not been directly connected to ROCK inhibition, neurite outgrowth and vinculin distribution were studied in rat hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%